Neural mechanisms of memory stability and flexibility in the human brain - Koolschijn, RS (2022)
The brain has the remarkable capacity to acquire, store, and reinstate memories. On the one hand, memories can be stored safely, free from interference. On the other hand, new memories are acquired daily, and can be used to update previously stored information. To safely store memories, a stable memory system is required, while for new learning flexibility and plasticity are needed. This means that the brain operates along a trade-off between memory stability and flexibility. In this thesis, I investigated the neural mechanisms that support stable and flexible memory, probing neocortical, hippocampal and neuromodulatory contributions. To study these different contributions, I have used techniques that measure and modulate cortical excitation and inhibition, in combination with behavioural and neural readouts of memory, with the aim to understand how neurochemistry and neural representations influence memory formation, storage and recall.